2015
DOI: 10.1016/j.canlet.2015.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Radiation takes its Toll

Abstract: The ability to recognize and respond to universal molecular patterns on invading microorganisms allows our immune system to stay on high alert, sensing danger to our self-integrity. Our own damaged cells and tissues in pathological situations activate similar warning systems as microbes. In this way, the body is able to mount a response that is appropriate to the danger. Toll-like receptors are at the heart of this pattern recognition system that initiates innate pro-oxidant, pro-inflammatory signaling cascade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 133 publications
0
24
0
Order By: Relevance
“… 44 , 94 , 95 A combination of several chemotherapeutic agents is currently used in treatment of PDAC, but unfortunately they have significant side effects, even though increasing life expectancy by 6 months. 96 , 97 Hence, there is a need to find other targets to treat PDAC. Transcriptional factors like nuclear factor of activated T-cells, Nrf2, and NFκB have been recently identified as potential targets to cure PDAC.…”
Section: Lipoxins and Their Clinical Relevancementioning
confidence: 99%
“… 44 , 94 , 95 A combination of several chemotherapeutic agents is currently used in treatment of PDAC, but unfortunately they have significant side effects, even though increasing life expectancy by 6 months. 96 , 97 Hence, there is a need to find other targets to treat PDAC. Transcriptional factors like nuclear factor of activated T-cells, Nrf2, and NFκB have been recently identified as potential targets to cure PDAC.…”
Section: Lipoxins and Their Clinical Relevancementioning
confidence: 99%
“…TLRs play major roles in antibacterial and antiviral immunity. Furthermore, recent studies have shown the involvement of TLRs in radiation response, including radiation-induced tissue damage and the efficacy of cancer radiotherapy [ 6 , 9 , 11 , 12 ]. We have previously reported that ionizing radiation affects the expressions and responses of TLR2 and TLR4 in human monocytic THP1 cells [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that TLR2–/– mice are more susceptible to ionizing radiation–induced mortality because of severe bone marrow cell loss, and wild-type mice pre-treated with TLR2 agonist show resistance to ionizing-induced motility [ 6 ]. In addition to the exogenous danger molecules PAMPs, TLRs recognize endogenous danger molecules, the so-called damage-associated molecular patterns (DAMPs) [ 8 , 9 ]. It has been shown that the responses of TLRs to DAMPs such as host RNA and high-mobility group box 1 (HMGB1), which are released from damaged cells, also cause biological responses, including the radiation response [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For radiation-induced lung injury it has been described that the released DAMPs act through signaling via P2X, P2Y receptors, toll-like receptors (TLR-2 and TLR-4), receptor for advanced glycation end-products, and NOD-like receptors (NLRP3), respectively (152). Consistent with a role of TLR signaling in radiation-induced lung disease, Myd88 knockout mice displayed increased as well decreased fibrosis development depending on the type of injury induced.…”
Section: Role Of Lymphocytes In the Irradiated Lungmentioning
confidence: 99%